Infective Endocarditis as a Complication of Intravenous Drug Use in Pregnancy: A Retrospective Case Series and Literature Review - Adebayo Adesomo; Veronica Gonzalez-Brown; Kara M. Rood (Thieme Medical Publishers, Inc., 2020)
Objective An increase in opioid use disorder and subsequent intravenous drug use has led to an increase in sequalae that may complicate pregnancy, such as infective endocarditis. Infective endocarditis has the potential for significant maternal and neonatal morbidity and mortality. We sought to examine the management considerations and clinical implications of intravenous drug use-related infective endocarditis in pregnancy from our center's experience. Study Design Retrospective study of management of pregnancies complicated by infective endocarditis as a result of active intravenous drug use at an academic tertiary care hospital from January 2012 through December 2019. Results Twelve women with active intravenous drug use histories were identified as having clinical and echocardiographic features consistent with infective endocarditis. Six women were discharged against medical advice and did not complete the full course of recommended antibiotic regimen. Eight women were started or continued on opioid agonist therapy during their hospitalization. Four neonates required neonatal intensive care unit admission for pharmacologic treatment for neonatal abstinence syndrome. Conclusion Management of intravenous drug use-associated infective endocarditis in pregnancy involves more than treating the acute condition. In pregnant women with opioid use disorder and infective endocarditis, addiction and chronic psychosocial conditions need to be addressed to optimize care.